Are glucose profiles well-controlled within the targets recommended by the International diabetes Federation in type 2 diabetes? A meta-analysis of results from continuous glucose monitoring based studies. (December 2018) - Paing, Aye C.; Kirk, Alison F.; Collier, Andrew; Kubiak, Thomas; Chastin, Sebastien F.M.
Abstract: Aims: To assess continuous glucose monitoring (CGM) derived intra-day glucose profiles using global guideline for type 2 diabetes recommended by the International Diabetes Federation (IDF). Methods: The Cochrane Library, MEDLINE, PubMed, CINAHL and Science Direct were searched to identify observational studies reporting intra-day glucose profiles using CGM in people with type 2 diabetes on any anti-diabetes agents. Overall and subgroup analyses were conducted to summarise mean differences between reported glucose profiles (fasting glucose, pre-meal glucose, postprandial glucose and post-meal glucose spike/excursion) and the IDF targets. Results: Twelve observational studies totalling 731 people were included. Pooled fasting glucose (0.81 mmol/L, 95% CI, 0.53–1.09 mmol/L), postprandial glucose after breakfast (1.63 mmol/L, 95% CI, 0.79–2.48 mmol/L) and post-breakfast glucose spike (1.05 mmol/L, 95% CI, 0.13–1.96 mmol/L) were significantly higher than the IDF targets. Pre-lunch glucose, pre-dinner glucose and postprandial glucose after lunch and dinner were above the IDF targets but not significantly. Subgroup analysis showed significantly higher fasting glucose and postprandial glucose after breakfast in all groups: HbA1c <7% and ≥7% (53 mmol/mol) and duration of diabetes <10 years and ≥10 years. Conclusions: Independent of HbA1c, fasting glucose and postprandial glucose after breakfast are not well-controlled in type 2 diabetes.